2016
DOI: 10.1097/acm.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Parental Leave During Graduate Medical Education

Abstract: Approximately 40% of respondents planned to have children during their GME training; most will require family leave and institutional support. GME programs should pursue policies and practices to minimize the effects of these leaves on their workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 34 publications
1
69
1
Order By: Relevance
“…3 Approximately 40% of GME respondents to a 2013 survey planned to have children during their training. 4 The increase in female trainees has challenged GME programs to accommodate the needs of parent trainees while meeting training requirements. Moreover, as GME programs attempt to meet the Accreditation Council for Graduate Medical Education (ACGME) Common Program Requirements for trainee well-being, innovative approaches are necessary to meet the needs of parent trainees as well as the training requirements of GME programs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Approximately 40% of GME respondents to a 2013 survey planned to have children during their training. 4 The increase in female trainees has challenged GME programs to accommodate the needs of parent trainees while meeting training requirements. Moreover, as GME programs attempt to meet the Accreditation Council for Graduate Medical Education (ACGME) Common Program Requirements for trainee well-being, innovative approaches are necessary to meet the needs of parent trainees as well as the training requirements of GME programs.…”
Section: Introductionmentioning
confidence: 99%
“…13,16 Residency is an arduous period, and female residents may be at a disadvantage for completing and publishing research, especially if they have additional family responsibilities. 18 Completing a research block had a statistically significant positive association with publication during residency. Research programs are known to generally result in increased participation in scholarly activity during residency.…”
Section: Discussionmentioning
confidence: 96%
“…This finding runs counter to the family orientation of our specialty and the fact that many ORIGINAL ARTICLES residency and academic medicine programs and organizations have called for family-friendly parental leave policies for faculty and residents. 3,16,24,[29][30][31] By surveying FM residency program directors about both policies and actual leave taken by recent residents and faculty members, our study begins to illustrate the interplay between policy and culture petaining to parental leave. This is important, as policies need to be supported by institutional and specialty culture in order to effectively protect time for new parents.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A 2013 resident physician survey of various disciplines at one institution reported that 41% had children, 7% were pregnant or had pregnant partners, and about 40% planned to have a first child or another child during residency. 3 This contrasts with a 1983 survey that found only 13% of married women had a child during residency. 4 The growing number of trainees who plan childbearing makes the topic of parental leave increasingly important for medical educators and for graduate medical education governing bodies that are responsible for developing policy and procedures that affect these professionals.…”
mentioning
confidence: 84%